URGENSI “MODERASI BERAGAMA” UNTUK MENCEGAH RADIKALISME DI INDONESIA - Bartolomeus Samho (Universitas Katolik Parahyangan, 2022)
This paper aims to describe the reasons behind the importance of “religious moderation” to prevent radicalism in Indonesia. The method used in this paper is literature study (books, journals, encyclopedias, and dictionaries). The results of this study indicate that